A networked rurality: social support and its community-based practices (Palimpsesto, 2026)
This study, conducted in Mendoza (Argentina), examines the dynamics of community social support networks as a key factor for strengthening communities and community health. It explores rural features shaping the networked nature of support, drawing on analyses of community integration and participation and comparing rural and urban contexts. Using the Perceived Community Social Support Questionnaire and field notes, and from a socio-critical perspective, the study adopts the notion of community entramado to describe diverse, tension-laden forms of reciprocity.
Keywords: social support; community networks; community weaving; rurality